Metabolic bone disease of prematurity - a report of five cases - Maria Inês Graça; Jorge Silva; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2019)
Metabolic bone disease of prematurity (MBDP) is a multifactorial condition characterized by a reduction in bone mineral density, involving chiefly nutritional but also biomechanical and hormonal factors. This is a relatively common complication among preterm infants, especially in those born before completing 28 weeks of gestation or those with extremely low birth weight (ELBW; < 1,000 g). These infants are prematurely deprived of calcium and phosphorus transplacental transfer, which is maximal during the third trimester of pregnancy and therefore present diminished mineral stores that may be further depleted by increased mineral requirements in the neonatal period. There are no standard approaches for the investigation and monitoring of MBDP and many cases remain undiagnosed until severe demineralization occurs. This entity is often clinically silent, being detected in laboratory studies or incidentally on radiographies performed for other purposes. We report five cases of premature infants diagnosed with MBDP in our neonatal intensive care unit (NICU) and discuss early prevention and detection of this disease. The primary prevention and treatment approach is based on early and adequate nutritional intervention by providing sufficient calcium and phosphorus intakes and vitamin D supplementation. Motor physiotherapy is also recommended. Despite these preventive strategies, some infants may still develop MBDP and require further supplementation. Considering the potential complications of MBDP, screening should target infants at high risk, including those with very low birth weight (VLBW, < 1,500 g), namely those born before 28 weeks of gestation, on total parenteral nutrition (TPN) for longer than 4 weeks, unable to reach full fortified feeds or exposed to drugs with deleterious effects on bone health.